REGISTER ANALYSIS OF THE CONVERSATIONS AMONG PETROLEUM ENGINEERS - Siti Nurani (IJEE (Indonesian Journal of English Education), 2014)
This present research aims at identifying register used in the conversations among petroleum engineers by examining the linguistic feature which is viewed from the aspect of the field, the tenor and the mode of discourse of the Systemic Functional Linguistics (SFL) approach. Findings show that in the field of discourse, all terms of register found in the experiential domain analysis function as technical terms, of which the two major forms of nouns and verbs (i.e., single-word and compound/phrasal word forms) are the most frequent categories identified among other kinds of technical terms. The goal orientation appears to have both short and long term while the social activity results in exchanges among participants. In the tenor of discourse, the agentive role is said to be equal and the social role is considered as non-hierarchic. The social distance within the interaction is said to be minimal which is excessively characterized by the use of informal form of expressions. In the mode of discourse, the language role exists equally of both constitutive and ancillary identified by the use of present simple tense and non-present tenses, that is, future simple, past simple and present perfect. The channel is in phonic form. The medium is in spoken with visual contact as it is largely characterized by the use of endophoric reference as well as pronouns.